Effectiveness of experiential learning-based teaching material in Mathematics - Mutmainah Mutmainah; Rukayah Rukayah; Mintasih Indriayu (Institute of Advanced Engineering and Science, 2019)
This research was aimed at finding out the effectiveness of experiential learning-based teaching material in Mathematics on the Mathematics cognitive ability of the fifth-grade student in elementary school. This research used quasi-experimental design involving two sample groups: experiment and control group. The sampling technique in this research used simple random sampling. The subject of this research was 54 students from the fifth-grade elementary school in Gunungpati Sub-district in the academic year 2017/2018. This study involved 28 students of the fifth-grade elementary school Nongkosawit 02 as the experimental group and 26 students of the fifth-grade elementary school Sadeng 03 as the control group. The instrument used in this research was multiple choice test consisting of 30 questions. The test was used to obtain pretest and posttest score.The data analysis in this research used T-independent test to examine the hypothesis. The result of the study shows the significance level of 0.000 is less than α = 0.05 which means that there is different cognitive ability between the experimental and control group. Thus, the use of experiential learning-based teaching material in Mathematics is effective to improve the Mathematics cognitive ability of the fifth-grade student in elementary school.